How are brands associated by users in short videos—A study on the mechanism of user associations with brand placements in short videos based on signal theory - Zhang Yang; Sun Dongqi (PLoS ONE, 2025)
The emergence of short video platforms has opened new avenues and opportunities for brand marketing. This paper investigates the mechanisms of brand dissemination in short videos, examining strategies for fostering brand associations to fulfill communication objectives. Drawing on signal theory, the study identifies the perceived value of short videos as the source of signals, with brand value and transparency serving as mediating factors, and brand association as the outcome. The research employs hypothesis testing and model building, supplemented by analysis of 560 valid questionnaires from research platforms, to scrutinize these mechanisms. Findings suggest that brand transparency and value effectively mediate the relationship between the perceived value and brand association, with brand transparency also mediating between perceived personality, utility, and brand association. Finally, this paper outlines management implications and acknowledges limitations based on the results.